Pengaruh Technology Usage, E- Networking Dan Government Support Terhadap Keberhasilan Entrepreneur Di Jakarta - Livia Livia; Kartika Nuringsih (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2020)
The purpose of this study is to examine the effect of technology usage, e- networking and government support to entrepreneur success in Jakarta. The sample as selected by a nonprobability sampling method of 100 respondens. The results of this study indicate that on technology usage, e –networking does not significantly influence the success of entrepreneurs in Jakarta and there is a significant on government support influence on the success of entrepreneurs in Jakarta. Tujuan dari penelitian ini adalah untuk menguji pengaruh technology usage, enetworking dan government support terhadap keberhasilan entrepreneur di Jakarta. Sampel dipilih menggunakan metode nonprobability sampling sebesar 100 responden. Hasil penelitian ini menunjukan bahwa pada technology usage dan e-networking tidak berpengaruh secara signifikan terhadap keberhasilan entrepreneur di Jakarta dan terdapat pengaruh yang signifikan pada government support terhadap keberhasilan entrepreneur di Jakarta